Polybutylene terephthalate composition and manufacturing method thereof

By controlling the crystal heat flow change rate of the PBT complex and the alcohol decomposition and butylene glycol transferrification reaction during the recovery process, the problems of high impurity content and poor thermal stability during PBT recovery were solved, and PBT complex with low impurity, high thermal stability and environmental protection performance were achieved.

JP2025058804AActive Publication Date: 2025-04-09CHANG CHUN PLASTICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023197229
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-28
Filing Date
2023-11-21
Publication Date
2025-04-09
Estimated Expiration
2043-11-21

AI Technical Summary

Technical Problem

When recycling polypropylene plates (PBT), the generated products have high impurities and poor thermal stability, making it difficult to meet the requirements of environmental protection and processing performance.

Method used

By controlling the crystal heat flow change rate in the range of 200-2300 mW/g-min during the recovery process of polypropylene ter plates (PBT), combined with alcohol decomposition and transesterification reaction of butanediol, PBT complex with low impurities and high thermal stability was prepared.

Benefits of technology

The PBT complex has achieved low impurities and high thermal stability, meets environmental protection process requirements, and improves its application in subsequent processing steps.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058804000001_ABST
    Figure 2025058804000001_ABST
Patent Text Reader

Abstract

To provide a polybutylene terephthalate composition and the manufacturing method thereof.SOLUTION: The present invention relates to a polybutylene terephthalate composition and the manufacturing method thereof. The change rate of crystallization heat flow of the polybutylene terephthalate composition is 200 mW / g-min or more, and the change rate of crystallization heat flow is determined according to the method of ISO 11357-3:2018. The polybutylene terephthalate composition of this invention has ideal heat resistance and low impurity content, and it is highly applicable in subsequent processing.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polybutylene terephthalate composition, and in particular to an environmentally friendly polybutylene terephthalate composition and a method for preparing the same, although the present application is not limited thereto. [Background technology]

[0002] Polyester is a general term for polymers that have ester functional groups in the main chain. It has properties such as light weight, impact resistance, tear resistance, and high transparency, and can be used for packaging various daily necessities. However, polyester is often used as a single-use or disposable packaging material, and is difficult to decompose, which causes serious environmental pollution. Therefore, the reuse of collected polyester products has become an important issue.

[0003] Currently used methods for recovering polyester can be divided into physical and chemical recovery. Chemical recovery involves depolymerizing polyester under certain reaction conditions to obtain basic polyester monomers or oligomers, which are then separated and purified before being polymerized again to produce new polymers, and can produce the particularly widely used polybutylene terephthalate (PBT). Chemical recovery can be further subdivided into hydrolysis, alcoholysis, and supercritical fluid extraction.

[0004] In the prior art, for example, Patent Document 1 discloses a method for preparing PBT using waste (recycled) PET and / or PBT, which includes melting PET polyester and / or PET-PBT blend polyester to obtain a melt, adding a depolymerization solution to perform depolymerization in a depolymerization vessel to obtain BHET and BHBT monomers, where the depolymerization solution contains 1,4-butanediol (BDO) and / or ethylene glycol (EG), and transesterifying the BHET and BHBT monomers with methanol to obtain a dimethyl terephthalate (DMT) solution, purifying the DMT solution to obtain purified DMT, transesterifying the purified DMT with BDO to obtain BHBT, and then condensing and polymerizing the BHBT to produce a PBT polymer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] China Patent Application Publication No. 114805766 Summary of the Invention [Problem to be solved by the invention]

[0006] In the prior art, when recycled polyester was used to regenerate polybutylene terephthalate (hereinafter referred to as PBT) compositions, the resulting products had high impurity content and poor heat resistance. In response to this, the present inventors discovered that by controlling the crystallization heat flow rate of the PBT composition within a specific range, it is possible to harmonize with the trend toward environmental considerations, while at the same time imparting good heat resistance to the PBT composition and reducing the impurity content. [Means for solving the problem]

[0007] Specifically, the PBT composition provided as one embodiment of the present invention is obtained by alcoholyzing a recycled polyester, and the recycled polyester has a structure represented by the following formula (i): [ka] wherein R1, R2, R3 and R4 are the same or different and each is hydrogen, an alkyl group having 1 to 6 carbon atoms, a halogen, an alkoxy group having 1 to 6 carbon atoms, an alkoxycarbonyl group having 2 to 6 carbon atoms, a nitrile group, an amino group, a sulfonyl group, a nitro group or a phenoxy group; X is a divalent aliphatic hydrocarbon group having 1 to 10 carbon atoms; Y is -OCO- or -O-; and n is an integer between 30 and 500; wherein the composition has a crystallization heat flow rate of 200 mW / g-min or more, and the crystallization heat flow rate is measured by a method based on ISO 11357-3:2018.

[0008] In one or more embodiments, the composition has a crystallization heat flow rate of 200-2300 mW / g-min.

[0009] In one or more embodiments, the recycled polyester is polyethylene terephthalate, polytrimethylene terephthalate, or polybutylene terephthalate.

[0010] In one or more embodiments, the PBT composition has a crystallization temperature (Tc) greater than 183°C.

[0011] In one or more embodiments, the composition contains less than 0.1 mol % residues of ethylene glycol (EG).

[0012] In one or more embodiments, the composition contains less than 0.1 mol % residues of diethylene glycol (DEG).

[0013] In one or more embodiments, the composition has an intrinsic viscosity (IV) of 0.5 to 1.5 dL / g.

[0014] Another aspect of the present invention provides a method for forming a PBT composition from reclaimed polyester, comprising the steps of: (1) providing a reclaimed polyester, the reclaimed polyester having a structure represented by formula (i): [ka] wherein R1, R2, R3 and R4 are the same or different and each is hydrogen, an alkyl group having 1 to 6 carbon atoms, a halogen, an alkoxy group having 1 to 6 carbon atoms, an alkoxycarbonyl group having 2 to 6 carbon atoms, a nitrile group, an amino group, a sulfonyl group, a nitro group or a phenoxy group, X is a divalent aliphatic hydrocarbon group having 1 to 10 carbon atoms, Y is -OCO- or -O-, and n is an integer between 30 and 500; and (2) adding an alcohol to alcoholyze the recovered polyester to obtain oligomers. (3) adding 1,4-butanediol (1,4-BDO) in several portions under negative pressure to carry out an ester exchange reaction with the oligomer to obtain a bis(2-hydroxylbutyl) terephalate (BHBT) prepolymer; and (4) polymerizing BHBT under a pressure of less than 1.5 mbar to obtain the PBT composition, wherein the PBT composition has a crystallization heat flow rate of 200 mW / g-min or more, and the crystallization heat flow rate is measured by a method based on ISO 11357-3:2018.

[0015] In one or more embodiments, in step (3), 1,4-butanediol (1,4-BDO) is added in 2 to 4 portions under the negative pressure to carry out a transesterification reaction with the oligomer.

[0016] In one or more embodiments, the recycled polyester is polyethylene terephthalate, polytrimethylene terephthalate, or polybutylene terephthalate. Effect of the Invention

[0017] The PBT composition of the present invention belongs to post-consumer recycled resin (PCR), which is in line with the trend of environmental consideration, and has ideal heat resistance and low impurity content, making it highly applicable in subsequent processing steps. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a schematic diagram of structural signal analysis during impurity analysis in one embodiment of the present invention, showing the PET structure, and the i signal represents the remaining EG components involved in polymerization. [Diagram 2] FIG. 1 is a conceptual diagram of structural signal analysis during impurity analysis in one embodiment of the present invention, showing poly(diethylene glycol terephthalate), PDET, where the k signal represents the DEG structure. [Diagram 3] FIG. 2 is a conceptual diagram of structural signal analysis during impurity analysis in one embodiment of the present invention, showing a PBT structure, in which signal a represents the structure of PBT and signal a′ represents the structure of a terminal alcohol group in the PBT structure. [Figure 4] FIG. 2 is a conceptual diagram of a DSC analysis result in one embodiment of the present invention, which is a conceptual diagram of an analysis of a crystal heat flow change rate. [Diagram 5] FIG. 2 is a conceptual diagram of a DSC analysis result in one embodiment of the present invention, in which the crystallization temperature is analyzed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] In order to describe the present invention in more detail and without any ambiguity, the following description is presented with reference to the embodiments and specific examples of the present invention, which are not the only forms of specific examples for carrying out or applying the present invention. In this specification and the appended claims, the terms "a" and "the" may be construed as plural unless otherwise indicated in the context.

[0020] Although the numerical ranges and parameters defining the present invention are all approximate, the relevant numerical values ​​in the specific examples are shown as precisely as possible. However, any numerical value will inherently contain standard deviations resulting from individual testing methods. Here, the term "about" means that the actual numerical value is within an acceptable standard error of the mean value when considered and determined by a person skilled in the art to which the present invention pertains.

[0021] The dash symbol "-", as used herein other than between two words or symbols, is used to represent a point of attachment of a substituent. For example, the dash symbol in -(C=O)CH3 represents a carbon bond through a carbonyl group (C=O).

[0022] [PBT composition] The PBT composition provided as one embodiment of the present invention is obtained by alcoholyzing recovered polyester, and the crystallization heat flow rate of the composition is 200 mW / g-min or more.

[0023] The above-mentioned "recycled polyester" refers to a polyester composition obtained through recovery, which has a structure represented by the following formula (i): [ka] where R1, R2, R3 and R4 are the same or different and each is hydrogen, an alkyl group having 1-6 carbon atoms, a halogen, an alkoxy group having 1-6 carbon atoms, an alkoxycarbonyl group having 2-6 carbon atoms, a nitrile group, an amino group, a sulfonyl group, a nitro group or a phenoxy group. The alkyl group is, but is not limited to, for example, a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an isobutyl group, an n-butyl group, a s-butyl group, a t-butyl group, an isopentyl group, an n-pentyl group, a neopentyl group or an n-hexyl group. The halogen is, but is not limited to, for example, a fluorine group, a chlorine group or a bromine group. Examples of the alkoxy group include, but are not limited to, methoxy, ethoxy, n-propoxy, isopropoxy, isobutoxy, n-butoxy, s-butoxy, t-butoxy, isopentyloxy, n-pentyloxy, neopentyloxy, and n-hexyloxy. Examples of the alkoxycarbonyl group include, but are not limited to, methoxycarbonyl, ethoxycarbonyl, n-propoxycarbonyl, isopropoxycarbonyl, n-butoxycarbonyl, isobutoxycarbonyl, s-butoxycarbonyl, t-butoxycarbonyl, n-pentyloxycarbonyl, isopentyloxycarbonyl, and neopentyloxycarbonyl. X is a divalent aliphatic hydrocarbon group having 1 to 10 carbon atoms, such as, but not limited to, methylene, dimethylene, trimethylene, tetramethylene, pentamethylene, hexamethylene, heptamethylene, octamethylene, nonamethylene, decamethylene, ethylene, propylene, methyltrimethylene, or butylene. Y is -OCO- or -O-. n is an integer between 30 and 500, for example, an integer between 50 and 70 or an integer between 100 and 200, and specifically, but not limited to, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, and 500.

[0024] According to some preferred embodiments of the present invention, the above-mentioned recycled polyester is recycled polyethylene terephthalate (hereinafter referred to as PET), polyethylene terephthalate (hereinafter referred to as PTT) or polyethylene terephthalate (polybutylene terephthalate, PBT). More preferably, recycled PET or PBT. According to some preferred embodiments of the present invention, the recycled polyester component (i.e., PCR content) in the PBT composition of the present invention can be 5 to 80 wt%, for example, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80 wt%, but is not limited thereto, and is preferably 60 wt%. The remaining components are, for example, but not limited to, other compound components that are added during the preparation process and are necessary for alcoholysis and transesterification of the recovered polyester, and may also be other components that are added separately to provide a wide range of performance and are necessary in the subsequent processing and formation of the product, such as additives, modifiers, or reinforcing agents, etc. Examples of additives include stabilizers (such as ultraviolet absorbers), antioxidants, heat stabilizers, lubricants, mold release agents, catalyst deactivators, nucleating agents, crystallization promoters, etc.

[0025] The above-mentioned "crystallization heat flow rate of change" is a parameter measured based on the standard method of ISO 11357-3:2018, which specifies a method for determining the temperature and enthalpy of melting and crystallization of crystalline or partially crystalline plastics. The method can be performed by differential scanning calorimetry (hereinafter referred to as DSC). More specifically, the change in the crystallization enthalpy (ΔHc) of the PBT composition is measured by a heating method with heat flow (units may be W / g, etc.) on the vertical axis and time (units may be min, etc.) on the horizontal axis, and the above-mentioned crystallization heat flow rate of change can be obtained by plotting a graph of the change in the crystallization heat flow curve and calculating the slope at the peak of the crystallization heat generation. More specifically, the above-mentioned heat flow is a value obtained by the heat transfer rate / mass of material, and the heat transfer rate refers to the amount of heat transferred from one object to another object per unit time. Without being limited to a particular theory, the present inventors have discovered that the rate of change of crystallization heat flow is a parameter that can be controlled by the preparation conditions of the PBT composition.

[0026] The present inventors have discovered that when the above-mentioned rate of change in crystallization heat flow is controlled within a specific range, the heat resistance of the PBT composition can be improved. Specifically, the PBT composition of the present invention has a crystallization heat flow rate of 200 mW / g-min or more, measured based on the method of ISO 11357-3:2018, and is not limited thereto, for example, 200 mW / g-min or more, 400 mW / g-min or more, 600 mW / g-min or more, 800 mW / g-min or more, 1000 mW / g-min or more, 1200 mW / g-min or more, 1400 mW / g-min or more, 1600 mW / g-min or more, 1800 mW / g-min or more, 2000 mW / g-min or more, 2200 mW / g-min or more, or 2400 mW / g-min or more, and preferably, the crystallization heat flow rate of the PBT composition is 200 to 2300 mW / g-min.

[0027] In some embodiments of the present invention, the crystallization temperature of the PBT composition of the present invention is greater than 183° C., specifically, for example, greater than 183° C., greater than 184° C., greater than 185° C., greater than 186° C., greater than 187° C., greater than 188° C., greater than 189° C., greater than 190° C., or greater than 191° C. Without being limited to a particular theory, it is believed that when the crystallization temperature of the PBT composition is greater than 183° C., it can exhibit better heat resistance in subsequent processing steps.

[0028] As used herein, "residues of ethylene glycol (hereinafter referred to as EG)" and "residues of diethylene glycol (DEG)" are impurities commonly found in PBT compositions formed by alcoholyzing recycled polyester. If the content of the impurities is too high, the processing properties of the PBT composition are deteriorated, affecting its applicability. In order to provide a PBT composition with better processing properties, according to some embodiments of the present invention, the PBT composition contains less than 0.1 mol% of EG residues or less than 0.1 mol% of DEG residues. Specifically, the EG residues or DEG residues contained in the PBT composition of the present invention are, for example, less than 0.1 mol%, less than 0.09 mol%, less than 0.08 mol%, less than 0.07 mol%, less than 0.06 mol%, less than 0.05 mol%, less than 0.04 mol%, less than 0.03 mol%, or less than 0.02 mol%, and preferably, the EG residues and DEG residues contained in the PBT composition are both less than 0.1 mol%.

[0029] According to some embodiments of the present invention, the intrinsic viscosity (IV) of the PBT composition is 0.5 to 1.5. Specifically, for example, it is between any two of the following values: 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, or 1.5. Compared with conventional resins that may have low intrinsic viscosities, the intrinsic viscosity of the PBT composition of the present invention is sufficiently high, so that applicability in subsequent processing steps can be ensured.

[0030] According to some embodiments of the present invention, the carboxylic end group (hereinafter referred to as CEG) content of the PBT composition is less than 50 meq / Kg based on the weight of the PBT composition. Specifically, for example, it is less than 50 meq / Kg, less than 40 meq / Kg, less than 30 meq / Kg, less than 20 meq / Kg, or less than 10 meq / Kg. Specifically, the CEG content is 15-21 meq / Kg based on the weight of the PBT composition. Compared with conventional polyesters having a relatively high CEG content, the PBT composition of the present invention has a low CEG content, exhibits higher hydrolysis resistance, is not easily decomposed in a high temperature and high humidity environment, and has excellent mechanical strength, so that the PBT composition can be ensured to be applicable in subsequent processing steps. More specifically, the PBT composition can be further formed into a molded article, and the molded article can be used for, but is not limited to, electronic products (e.g., laptop computer cases, keyboard and mouse cases, etc.), bottle containers, packaging materials, automobile and component materials, shoe sole base materials, etc., or the molded article can be woven into polyester fibers that can be used to manufacture clothing, curtains, etc.

[0031] [Method of preparing PBT composition] Another aspect of the present invention provides a method for forming a PBT composition from recovered polyester, the method comprising the steps of: (1) providing the recovered polyester; (2) adding an alcohol to alcoholyze the recovered polyester to form an oligomer or monomer; (3) adding 1,4-butanediol (1,4-BDO) in portions under negative pressure to effect transesterification with the oligomer to obtain a bis(2-hydroxylbutyl)terephalate prepolymer (hereinafter referred to as BHBT); and (4) polymerizing the BHBT under a pressure of less than 1.5 mbar to obtain the PBT composition, the PBT composition having a crystallization heat flow rate of 200 mW / g-min or more, the crystallization heat flow rate being measured according to a method based on ISO 11357-3:2018.

[0032] More specifically, the recovered polyester has a structure represented by the following formula (i): [ka] where R1, R2, R3 and R4 are the same or different and each is hydrogen, an alkyl group having 1-6 carbon atoms, a halogen, an alkoxy group having 1-6 carbon atoms, an alkoxycarbonyl group having 2-6 carbon atoms, a nitrile group, an amino group, a sulfonyl group, a nitro group or a phenoxy group. The alkyl group is, but is not limited to, for example, a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an isobutyl group, an n-butyl group, a s-butyl group, a t-butyl group, an isopentyl group, an n-pentyl group, a neopentyl group or an n-hexyl group. The halogen is, but is not limited to, for example, a fluorine group, a chlorine group or a bromine group. Examples of the alkoxy group include, but are not limited to, methoxy, ethoxy, n-propoxy, isopropoxy, isobutoxy, n-butoxy, s-butoxy, t-butoxy, isopentyloxy, n-pentyloxy, neopentyloxy, and n-hexyloxy. Examples of the alkoxycarbonyl group include, but are not limited to, methoxycarbonyl, ethoxycarbonyl, n-propoxycarbonyl, isopropoxycarbonyl, n-butoxycarbonyl, isobutoxycarbonyl, s-butoxycarbonyl, t-butoxycarbonyl, n-pentyloxycarbonyl, isopentyloxycarbonyl, and neopentyloxycarbonyl. X is a divalent aliphatic hydrocarbon group having 1 to 10 carbon atoms, such as, but not limited to, methylene, dimethylene, trimethylene, tetramethylene, pentamethylene, hexamethylene, heptamethylene, octamethylene, nonamethylene, decamethylene, ethylene, propylene, methyltrimethylene, or butylene. Y is -OCO- or -O-. n is an integer between 30 and 500, for example, an integer between 50 and 70, or an integer between 100 and 200.

[0033] According to some preferred embodiments of the present invention, the recycled polyester is recycled polyethylene terephthalate (hereinafter referred to as PET), polyethylene terephthalate (hereinafter referred to as PTT) or polyethylene terephthalate (polybutylene terephthalate (PBT). More preferably, it is recycled PET or PBT.

[0034] The term "alcohols" as used herein refers to alcohols capable of alcoholically decomposing the recovered polyester into oligomers or monomers, and are considered to be depolymerization agents used to decompose the polyester chains. Typically, these are low molecular weight alcohols such as, but not limited to, methanol, ethylene glycol, 1,4-BDO, and the like, with 1,4-BDO or methanol being a preferred embodiment.

[0035] The term "oligomer" as used herein refers to a polymer composed of a relatively small number of repeating units. In step (2) of the method of the present invention, the recovered polyester is reacted with an alcohol to alcoholize the recovered polyester into oligomers or monomers, which facilitates the subsequent transesterification reaction. This specification does not limit the conditions for the alcoholysis reaction.

[0036] In step (3), 1,4-BDO is added to the oligomer in several portions under negative pressure conditions to carry out an ester exchange reaction, thereby obtaining BHBT. In detail, the number of times that the 1,4-BDO is added in portions (i.e., the number of times that the ester exchange reaction is carried out) is at least two. Although not limited to a particular theory, adding 1,4-BDO in several portions is one of the variables for controlling the crystallization heat flow change rate within a desired range, and the number of times that the 1,4-BDO is added in portions is preferably 2 to 4 times, more preferably 2 times. The above-mentioned "negative pressure" pressure conditions refer to pressure conditions lower than atmospheric pressure (i.e., 1013 mbar), and are, for example, less than 1013 mbar, less than 800 mbar, less than 600 mbar, less than 400 mbar, or less than 200 mbar. Without being limited to a particular theory, the pressure condition of the negative pressure is one of the variables that control the crystallization heat flow change rate within a desired range, and the negative pressure is preferably 145 mbar or 100 mbar. The above-mentioned "prepolymer" refers to a substance obtained by prepolymerizing a monomer or oligomer, and when it is difficult to completely polymerize the monomer or oligomer in one go to form a polymer, forming a prepolymer first can make it easier to carry out the subsequent polymerization reaction. In the above-mentioned transesterification and polymerization reaction, a catalyst can be added, for example, at least one catalyst selected from manganese acetate, calcium acetate, and zinc acetate as a transesterification reaction catalyst, or a catalyst that can be used in a polymerization reaction, such as antimony trioxide, tetrabutyl orthotitanate, n-butyltin hydroxide, or monobutyltin tri(2-ethylhexanoate).

[0037] Without being limited to a particular theory, the pressure conditions under which the BHBT is polymerized in step (4) are one of the variables that control the crystal heat flow rate within a desired range, and preferably, the pressure conditions are high vacuum pressure conditions, for example, 0.5, 1, 1.5 or 2 mbar, and more preferably less than 1.5 mbar. EXAMPLES

[0038] The present invention will be described in more detail below with reference to specific examples. However, it should be understood that the specific examples are provided to help the present invention be more easily understood, and are not intended to limit the scope of the present invention.

[0039] 1. Manufacturing method of PBT composition The methods for producing the PBT compositions of the present invention are provided in Examples 1 to 8 and Comparative Examples 1 to 4.

[0040] The main steps for preparing the PBT compositions of the present embodiment and the comparative embodiment are as follows, and Table 1 below details the differences in one or more process parameters between the present embodiment and the comparative embodiment.

[0041] First, the recovered PET is subjected to an alcoholysis reaction once with 1,4-BDO of a specific equivalent (specifically, as shown in Examples 1-7 and Comparative Examples 1-4 in Table 1) or to an alcoholysis reaction once with methanol (MeOH) of a specific equivalent (specifically, as shown in Example 8 in Table 1) to obtain an oligomer or monomer. Next, 1,4-BDO of a specific equivalent (specifically, as shown in Table 1) is added to the oligomer in several batches (specific times as shown in Table 1) under specific pressure conditions (specific pressure conditions as shown in Table 1), and an ester exchange reaction (specific reaction time as shown in Table 1) is carried out to obtain BHBT. Finally, the BHBT is polymerized under pressure conditions of less than 1.5 mbar (i.e., high vacuum conditions) to form the PBT composition. Comparative Example 4 was carried out under the same conditions as Example 4 (invention 4) of US5,266,601.

[0042] [Table 1] JPEG2025058804000007.jpg100143

[0043] 2.Analysis method Here, the analysis and measurement methods of the PBT compositions of the above-mentioned Examples 1 to 8 and Comparative Examples 1 to 4 of the present invention are provided.

[0044] [Intrinsic Viscosity Analysis] The inherent viscosity analysis of the present invention was measured according to the standard method of ASTM D4603.

[0045] [Analysis of CEG content] The CEG content of the present invention was measured by titration. An ethanolic potassium hydroxide solution (potassium hydroxide concentration 0.05M) was used to titrate a PBT composition solution dissolved in o-cresol, in which potassium chloride (KCl) was present at a concentration of 0.01M.

[0046] [Analysis of impurities] 1. Sample preparation: The PBT composition was dissolved in a mixture of deuterated chloroform / trifluoroacetic acid-d (v / v=3 / 1) at a concentration of 10 mg / mL. 2.Analytical equipment: 1 Analysis was carried out by H-NMR (400 MHz). 3. Analysis method: Please refer to FIG. 1. In the figure, i represents the structural signal of the EG residue remaining in the PET structural signal and involved in polymerization, with a chemical shift between 4.82 and 4.78 ppm, and the number of hydrogen atoms is 4. Please refer to FIG. 2. In the figure, k represents the structural signal of the DEG residue remaining in the PET structural signal and involved in polymerization, with a chemical shift between 4.16 and 4.06 ppm, and the number of hydrogen atoms is 4. Please refer to FIG. 3. In the figure, a represents the structural signal of the PBT, with a chemical shift between 2.16 and 1.96 ppm, and the number of hydrogen atoms is 4. A' represents the structural signal of the terminal alcohol group in the PBT structure, with a chemical shift between 3.93 and 3.83 ppm, and the number of hydrogen atoms is 2. The above are the structural signals of the total diol structure in the product, and then the ratio of EG and DEG residues in the total diol structure was calculated according to the following formula.

number

number

[0047] [DSC analysis] 1. Standard method: The crystallization heat flow rate and crystallization temperature were measured according to the standard method of ISO 11357-3:2018. 2. Analytical equipment: Differential scanning calorimetry (hereinafter referred to as DSC) 3.Analysis process: a. Crystal heat flow rate of change Step 1: 10±0.2 mg of a sample (PBT composition) was placed in an aluminum pan and placed in the DSC, and a graph of the change in crystal heat flow was plotted according to the heat flow (unit: W / g) versus time. Specific temperature and time control are as described in steps 2 to 5. Step 2: The sample was heated to 280°C at a heating rate of 10°C / min, and the temperature was maintained for 3 minutes. Step 3: The temperature was lowered to 189°C at a heating rate of 5°C / min. Step 4: The temperature was maintained at 189°C for 30 minutes, and the crystal heat flow change rate was calculated. Step 5: The temperature was lowered to 0°C at a heating rate of 10°C / min, and the analysis was completed. For a specific method of calculating the crystal heat flow change rate in step 4, please refer to FIG. 4. The peak represents the crystallization process of the sample, and the slope (crystal heat flow / time) during heat generation is the crystal heat flow change rate, which can be calculated by the following formula.

number

[0048] 3. Evaluation method and results [Evaluation of plastic heat deflection testing (HDT)] 1. Standard methods: Analyses were performed according to the standard methods ISO 75-1 and ISO 75-2. 2.Analytical equipment: TOYOSEIKI No.533 HDT Tester 3. Analysis conditions: The HDT temperature of the sample was measured and recorded under each of the bending stresses of 0.45 MPa and 1.8 MPa. Generally, the heat distortion temperature (hereinafter referred to as HDT temperature) is related to the environmental pressure or load to which the material (sample) is placed. Therefore, when analyzing the HDT of a material according to the standard method of ASTM D648 or ISO 75-1 and ISO 75-2, the HDT temperature of the material is measured under bending stresses of 0.45 MPa (simulating no pressure load) and 1.8 MPa (simulating a constant pressure load) in order to better represent the heat resistance of the material. In addition, generally, the HDT temperature measured under bending stress of 0.45 MPa is higher than the HDT temperature measured under bending stress of 1.8 MPa. In addition, the higher the HDT temperature measured under the same conditions, the better the heat resistance of the material under those conditions. 4.Analysis process: Step 1: The sample particles were dried for 3 hours under the condition of 140°C. The sample particles were PBT compositions containing 30 wt.% glass fiber, which simulated the conditions of use of the PBT composition afterwards. Step 2: After drying the sample particles, an ISO standard test piece (80mm*10mm*4mm) was molded. Step 3: The sample test piece was left in an environment of 23±2°C and 50±5%RH (relative humidity) for at least 40 hours. Step 4: The sample test piece was annealed for 2 hours under the condition of 190°C, and then cooled to room temperature by standing. Step 5: The sample test piece after annealing was placed in an analytical instrument with the parameters (maximum temperature, pressure load) set. Step 6: When the sample test piece reached the deformation amount, the analytical instrument automatically stopped and the temperature was lowered. In addition, at least two data were obtained for one sample and averaged.

[0049] Furthermore, the intrinsic viscosity, CEG content, EG residue, DEG residue, crystallization temperature, PCR level, crystallization heat flow rate change rate, and plastic heat distortion test (HDT) evaluation results of the PBT compositions of Examples 1 to 8 and Comparative Examples 1 to 4 of the present application are summarized in Table 2.

[0050] [Table 2]

[0051] According to Table 2, it can be seen that the crystallization heat flow change rates of the PBT compositions of Examples 1 to 8 are all 200 mW / g-min or more, and the HDT temperatures of these PBT compositions under two conditions of 1.8 MPa and 0.45 MPa were all higher than those of Comparative Examples 1 to 4, whose crystallization heat flow change rates were not within the desired range. This shows that the heat resistance of the PBT composition can be improved only when the crystallization heat flow change rate of the PBT composition is controlled to 200 mW / g-min or more. In addition, the data in Table 2 shows that the PBT compositions of the examples of the present invention are in line with the trend toward environmental consideration, have low impurity content, and have good processing applicability (for example, but not limited to, ideal intrinsic viscosity and CEG content values).

[0052] In summary, the PBT composition of the present invention is a post-consumer recycled resin (PCR) that is in line with the trend toward environmental friendliness, has ideal heat resistance, and has a low impurity content, making it highly applicable in subsequent processing steps.

[0053] All ranges provided herein are meant to include each specific range within the assigned range and the combination of subranges between the assigned ranges. Also, unless otherwise stated, all ranges provided herein include the endpoints of the range. Thus, the range 1-5 specifically includes 1, 2, 3, 4, and 5, as well as subranges such as 2-5, 3-5, 2-3, 2-4, 1-4, etc.

[0054] All publications and patent applications referenced in this specification are hereby incorporated by reference, and each and every publication or patent application is specifically and individually indicated to be incorporated by reference herein for all purposes. In the event of a conflict between this specification and any publication or patent application incorporated by reference herein, the specification shall control.

Claims

1. A polybutylene terephthalate (PBT) composition is obtained by alcoholyzing a recycled polyester, the recycled polyester having a structure represented by the following formula (i): 【Chemistry 1】 where R 1 , R 2 , R 3 and R 4 are the same or different and each is hydrogen, an alkyl group having 1 to 6 carbon atoms, a halogen, an alkoxy group having 1 to 6 carbon atoms, an alkoxycarbonyl group having 2 to 6 carbon atoms, a nitrile group, an amino group, a sulfonyl group, a nitro group, or a phenoxy group; X is a divalent aliphatic hydrocarbon group having 1 to 10 carbon atoms; Y is -OCO- or -O-; and n is an integer between 30 and 500; The polybutylene terephthalate composition has a crystallization heat flow rate of 200 mW / g-min or more, and the crystallization heat flow rate is measured by a method based on ISO 11357-3:2018.

2. 2. The PBT composition of claim 1, wherein the composition has a crystallographic heat flow rate of 200 to 2300 mW / g-min.

3. 2. The PBT composition of claim 1, wherein the recycled polyester is polyethylene terephthalate, polytrimethylene terephthalate, or polybutylene terephthalate.

4. 2. The PBT composition of claim 1, having a crystallization temperature (Tc) greater than 183°C.

5. 10. The PBT composition of claim 1, wherein the composition contains less than 0.1 mol% residues of ethylene glycol (EG).

6. 10. The PBT composition of claim 1, wherein the composition contains less than 0.1 mol% residues of diethylene glycol (DEG).

7. The PBT composition of claim 1, wherein the composition has an intrinsic viscosity (IV) of 0.5 to 1.5 dL / g.

8. 1. A method for forming a PBT composition from recycled polyester, comprising the steps of: (1) preparing the recovered polyester, the recovered polyester having a structure represented by the following formula (i): 【Chemistry 2】 where R 1 , R 2 , R 3 and R 4 are the same or different and each is hydrogen, an alkyl group having 1 to 6 carbon atoms, a halogen, an alkoxy group having 1 to 6 carbon atoms, an alkoxycarbonyl group having 2 to 6 carbon atoms, a nitrile group, an amino group, a sulfonyl group, a nitro group, or a phenoxy group, X is a divalent aliphatic hydrocarbon group having 1 to 10 carbon atoms, Y is -OCO- or -O-, and n is an integer between 30 and 500; (2) adding an alcohol to alcoholyze the recovered polyester into an oligomer or a monomer; (3) adding 1,4-butanediol (1,4-BDO) in several portions under negative pressure to carry out an ester exchange reaction with the oligomer to obtain bis(2-hydroxybutyl)terephthalate prepolymer (bis(2-hydroxybutyl)terephthalate, BHBT); (4) polymerizing the BHBT under a pressure of less than 1.5 mbar to obtain the PBT composition, wherein the PBT composition has a crystallization heat flow rate of 200 mW / g-min or more, the crystallization heat flow rate being measured according to a method based on ISO 11357-3:2018.

9. The method according to claim 8, wherein in the step (3), 1,4-butanediol (1,4-BDO) is added in 2 to 4 portions under the negative pressure to carry out a transesterification reaction with the oligomer.

10. The method of claim 8, wherein the recovered polyester is polyethylene terephthalate, polytrimethylene terephthalate, or polybutylene terephthalate.

Citation Information

Patent Citations

  • Process for preparing polybutylene terephthalate from pet scrap

    US5266601A

  • Method for preparing PBT (Polybutylene Terephthalate) from PBT and waste PET (Polyethylene Terephthalate) polyester thereof or / and PET-PBT mixed polyester

    CN114805766A